At the Epicenter of a Community-wide Effort to Improve Public Health - Yolanda G. Martinez; Cheri Rufener (University of North Florida, 2014)
This paper describes the All Into Health Project implemented between 2010 and 2012 as part of the Communities Putting Prevention to Work initiative to address smoking in Orange County, Florida. The All Into Health Project exemplifies what can be accomplished through a combination of leadership and community organization. This demonstration project may inspire initiatives elsewhere that can lead to Florida becoming a comprehensive tobacco- free state.